The Impact Of Sustainable Manufacturing Practices On Sustainability - Norsiah, Hami; Mohd Razali, Muhamad; Zuhriah, Ebrahim (Penerbit UTM Press, 2016)
This study aims to empirically investigate the impact of sustainable manufacturing practices (SMP) on sustainability performance (SP) among manufacturing firms in Malaysia. Drawing from the theoretical lenses of stakeholder theory, the present study advocates the three pillars of sustainability, encompassing economic, environmental, and social sustainability, in measuring firm performance. Using PLS-SEM approach, the survey data collected from 150 firms were analyzed. The findings reveal that both underlying variables of SMP, internal SMP and external SMP, have positive and significant impact on environmental and social sustainability. Surprisingly, while internal SMP proof the significant positive influence on economic sustainability, external SMP failed to do so. Theoretically, the study contributes to the sustainable manufacturing literature by demonstrating the relationship between SMP and sustainability performance (SP). Practically, the study is beneficial for practitioners in understanding the diverse aspects of SMP and SP, identifies the strengths and weaknesses of their current SMP, and provides a guideline in improving their performance.